Evaluation of the mummification treatment at Conservative Dentistry Clinics - Rahmawati, Ayunda Dwi; Nasserie, Wazillah; Adang, Rahmi Alma Farah (Padjadjaran Journal of Dentistry, 2012)
Indonesia is one of many developing countries with high caries prevalence which needs more attention regarding the countermeasures as well as the preventive treatment. Dental problems or pulp injury was able to treated with an endodontic procedure such as pulpotomy. The success of the mummification treatment was able to evaluated through subjective and objective examinations. The purpose of this study was to describe an evaluation of the mummification treatment at Conservative Dentistry Clinics of Faculty of Dentistry Universitas Padjadjaran by examining the condition of the teeth that have received mummification treatment. This study was a descriptive study with purposive sampling technique. The number of samples was as much as 38 teeth from patients who have completed mummification treatment. The results showed the success of mummification treatment was as much as 67% in less than three months, 44% in the range of time 3-6 months, and 29% in more than 6 months. The conclusion of this study was the mummification treatment success at Conservative Dentistry Clinics of Faculty of Dentistry Universitas Padjadjaran was high in less than three months and decreasing in more than six months after treatment.